Spatial Development of Regions of Ukraine: Methodology of Geohistorical Analysis - Vermenych, Ya. V. (Ukrainian Geographical Journal, 2026)
The purpose of the study is to demonstrate the potential of geohistorical and geocultural approaches for analyzing the spatial development of regions in Ukraine. In the modern context of geopolitics and geoeconomics, these approaches provide a basis for forming a new image of areas and their territorial structures, considering geographical, linguistic, cultural, and religious characteristics, as well as specific regional identity. The novelty of the study lies in its analysis of strategies for analyzing regional systems, the ratios of regional to national values, and the formation of regional identity through the use of geohistorical methodological concepts. It has been shown that, under conditions of awareness of their regions’ self-sufficiency and capacity for self-development, geocultural approaches are no less effective than geoeconomic ones, providing an understanding of the uniqueness of the country’s cultural space, regional personality types, and communication methods. In the context of modern transformations of globalization, geohistorical and geocultural approaches to the study of spatial specificity are gaining momentum and offer opportunities to develop cultural and mental models of space and to interpret territory as a sociocultural integrity with its own unique pace of development.
Keywords: region; spatial development; geohistory; geoculture; limology